2016
DOI: 10.1021/acs.biochem.5b01298
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of a Copper-Binding Mutant of the Organomercurial Lyase MerB: Insight into the Key Role of the Active Site Aspartic Acid in Hg–Carbon Bond Cleavage and Metal Binding Specificity

Abstract: In bacterial resistance to mercury, the organomercurial lyase (MerB) plays a key role in the detoxification pathway through its ability to cleave Hg-carbon bonds. Two cysteines (C96 and C159; Escherichia coli MerB numbering) and an aspartic acid (D99) have been identified as the key catalytic residues, and these three residues are conserved in all but four known MerB variants, where the aspartic acid is replaced with a serine. To understand the role of the active site serine, we characterized the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…4749 Finally, substituting serine in place of D99 in E. coli MerB results in a mutant protein that sequesters Cu II when expressed in bacteria and has significantly lower catalytic activity. 50 Taken together with our current results on organotin and organolead compounds, initial binding to D99 is important not only for the catalytic activity of MerB, but also for metal selectivity.…”
Section: Discussionsupporting
confidence: 73%
“…4749 Finally, substituting serine in place of D99 in E. coli MerB results in a mutant protein that sequesters Cu II when expressed in bacteria and has significantly lower catalytic activity. 50 Taken together with our current results on organotin and organolead compounds, initial binding to D99 is important not only for the catalytic activity of MerB, but also for metal selectivity.…”
Section: Discussionsupporting
confidence: 73%
“…The 13 MerB-like 99Ser variants were identified in genomes that all contain at least one MerB with the aforementioned canonical sequence signatures; these genomes belonged to members of the bacterial phylum Firmicutes. Previous structural and biochemical characterization of representatives of the 99Ser MerB-like variants ( Wahba et al, 2016 ) has shown that they have expanded range of affinities for metals relative to canonical MerB. Specifically, this variant has an affinity to bind Cu(II) that is displaced by Hg(II) when present.…”
Section: Resultsmentioning
confidence: 99%
“…Hg(II) is a product of MerB-dependent demethylation of MeHg, and MerB binds Hg(II) so that it cannot diffuse into the cytoplasm; MerA then extracts the metal for reduction ( Wahba et al, 2016 ). The physiological role of these variant enzyme with an affinity for other divalent metals is thus not well understood especially when a native MerB 99Ser, in B. megaterium MerB2, does not bind Cu(II) ( Wahba et al, 2016 ). However, it is possible that they function as more generalized organic metalloid detoxification enzymes than canonical MerB.…”
Section: Resultsmentioning
confidence: 99%
“…FACETS | 2018 | 3: 858-879 | DOI: 10.1139/facets-2018-0015 861 facetsjournal.com Recent work on MerB has shown that conserved cysteine and aspartic acid residues are essential for releasing Hg from MerB's active site following the cleaving of the methyl group (Silva and Rodrigues 2015). When a serine residue was present in place of aspartic acid, MerB lost its specificity for MeHg and was also able to bind copper (Cu), although resupplying MerB with Hg successfully removed Cu from the enzyme's active site (Wahba et al 2016). These findings demonstrate that MeHg can outcompete Cu for the binding site on MerB, but also highlight functional parallels that may exist between RD and Cu homeostasis that merit further investigation.…”
Section: Grégoire and Poulainmentioning
confidence: 99%